COMPENSATION PAYMENTS FOR HEALTHCARE WORKERS: AN ANALYTICAL AND POLICY-ORIENTED REVIEW OF FINANCIAL PROTECTION MECHANISMS IN THE MEDICAL SECTOR - Mamadaliyev Avaz Abduraximovich (Bright Mind Publishing, 2025)
Compensation payments for healthcare workers represent a critical component of occupational protection systems, aimed at mitigating the financial, social, and health-related consequences of professional risks inherent in medical practice. Healthcare personnel are routinely exposed to biological, chemical, physical, ergonomic, and psychosocial hazards that significantly exceed those encountered in many other occupational sectors, resulting in increased rates of occupational diseases, work-related injuries, and long-term disability. This analytical and policy-oriented review examines the rationale, structure, and effectiveness of compensation payment mechanisms for medical workers, based on a comprehensive analysis of international and regional scientific literature complemented by hypothetical analytical modeling. The study explores compensation frameworks related to occupational diseases, workplace injuries, hazardous working conditions, and extraordinary professional risks, including epidemic and emergency response activities. Particular attention is given to high-risk medical environments such as surgical departments, emergency medical services, intensive care units, and diagnostic laboratories, where the need for adequate financial protection is especially pronounced. The findings indicate that compensation payments play a crucial role not only in supporting affected healthcare workers but also in maintaining workforce stability, motivation, and retention. However, the analysis reveals substantial disparities in compensation coverage, eligibility criteria, and payment adequacy, often resulting from fragmented regulatory approaches and insufficient alignment between occupational risk and financial compensation. The study concludes that the development of transparent, evidence-based, and risk-adjusted compensation systems is essential for ensuring social justice, protecting healthcare workers’ rights, and strengthening the resilience of healthcare systems.
Keywords: Healthcare workers, compensation payments, occupational risk, professional protection, workplace hazards, health policy.